Islamic Financial Literacy Socialization at Pesantren Terpadu Semayoen Nusantara - Riyaldi, Muhammad Haris; Farma, Junia; Najla, Najla; Umuri, Khairil; Muftahuddin, Muftahuddin (Universitas Syiah Kuala, 2025)
This activity aims to enhance the understanding and skills of pesantren administrators and students in managing Islamic finance, including the principles of Sharia-based financial management and the integration of digital financial technology. The event took place on Saturday, August 24, 2024, at Pesantren Terpadu Semayoen Nusantara, using a service learning (SL) approach that involved all stakeholders of the pesantren as active participants. Evaluation through pre-tests and post-tests showed significant improvement in participants' understanding, with a notable increase in their comprehension of Islamic finance principles after the activity. Participants also demonstrated a better readiness to apply Islamic financial literacy concepts into real-life practice, such as implementing Sharia-compliant financial management within the pesantren. These results are consistent with previous studies that highlight the critical role of education and capacity building in promoting the adoption of Islamic financial systems within the community.This activity contributes to the SDG's goals, particularly Goal 4 (Quality Education) and Goal 8 (Decent Work and Economic Growth), by equipping the pesantren community with knowledge and skills to manage finances ethically and effectively. Despite challenges such as time constraints, this activity successfully achieved its objectives and inspired the implementation of similar programs in the future.